Ambiguity in dynamic contracts - Martin Szydlowski (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2012)
I study a dynamic principal agent model in which the effort cost of the agent is unknown to the principal. The principal is ambiguity averse, and designs a contract which is robust to the worst case effort cost process. Ambiguity divides the contract into two regions. After sufficiently high performance, the agent reaches the over-compensation region, where he receives excessive benefits compared to the contract without ambiguity, while after low performance, he enters the under-compensation region. Ambiguity also causes a disconnect between the current effort cost and the strength of incentives. That is, even when the agent is under-compensated, his incentives are as strong as in the over-compensation region, since the principal fears the agent might shirk otherwise. Under ambiguity, the agent's true effort cost does not need to equal the worst-case. analyze the agent's incentives for this case, and show that the possibility of firing is detrimental to the agent's incentives. I study several extensions concerning the timing structure and the nature of the principal's ambiguity aversion.
Keywords: D82; D86; M52; 330; dynamic contract; principal-agent model; ambiguity aversion; continuous time